The SI Unit Candela. Issue 5 (15th January 2019) - Sperling, Armin; Kück, Stefan
Abstract: The history of photometry, the measurement of light—and thus also the root of the basic unit for the luminous intensity, goes back to the seventeenth century. The theoretical foundations are provided by Johann H. Lambert in his treatise on photometry around 1760. With industrialization in the nineteenth century, there is an increasing demand for stable reference light sources for the measurement of light and for an reliable definition of the unit for light. But it is not until the middle of the twentieth century that the basic prerequisites had been created to use a common, internationally recognized unit, the Candela, as a measure of the visible light. The following article describes the basics and the boundary conditions that arise for the unit candela from the revision of the SI. Abstract : The unit candela for the photometric quantity of luminous intensity is one of six units originally launched by the General Conference on Weights and Measures (CGPM) to build a coherent system of base units, later referred to as the International System of Units (SI). The boundary conditions valid after the revision of the SI and their basics are described here.